1989
DOI: 10.1111/j.1471-4159.1989.tb08546.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Stimulates Norepinephrine Uptake in PC12 Cells

Abstract: This study examined the effects of extracellular ATP on norepinephrine (NE) uptake, using PC12 cells as a model of noradrenergic neurons. Previous experiments with synaptosomes led to the hypothesis that extracellular ATP can regulate NE uptake via an ecto-protein kinase. In the present study, we examined the high-affinity uptake of NE (referred to as uptake 1) in PC12 cells in the presence of varying concentrations of extracellular ATP. In the presence of Ca2+, low concentrations of ATP (0.1 microM) increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Our previous studies have demonstrated that extracellular ATP can stimulate the highaffinity uptake of norepinephrine in PC12 cells (Hardwick et al, 1989). Norepinephrine uptake is the major means of transmitter inactivation at noradrenergic nerve terminals, requiring either Mgz+ or Ca2+ (Hendley, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have demonstrated that extracellular ATP can stimulate the highaffinity uptake of norepinephrine in PC12 cells (Hardwick et al, 1989). Norepinephrine uptake is the major means of transmitter inactivation at noradrenergic nerve terminals, requiring either Mgz+ or Ca2+ (Hendley, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The identification, localization, and characterization of specific endogenous protein substrates for phosphorylation activity are important for determining the physiological function of various protein kinases (Kennedy, 1983;Ehrlich, 1984Ehrlich, , 1987. Thus, the identification and characterization of the specific surface membrane proteins phosphorylated by extracellular ATP should provide insight into the mechanisms by which ecto-protein kinases are involved in the regulation of various neuronal functions (Ehrlich et al, 1986Ehrlich, 1987;Hendley et al, 1988;Muramoto et al, 1988;Hardwick et al, 1989).…”
mentioning
confidence: 99%
“…For example, axoplasmic transport delivers key vesicular proteins from their site of synthesis in the cell body to the terminals; thus, vesicular uptake could also be reduced by structural or functional abnormalities of axonal trafficking that decrease the number of vesicles available. Alternatively, cell membrane and vesicular monoamine transport are energy-requiring processes (28,29), and intrinsic errors of mitochondrial function or metabolic insults posed by exogenous toxins could result in decreased neuronal uptake and vesicular sequestration. Moving forward, bases for the deficit in vesicular 18 F-DA uptake will need to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…7). Ectoprotein kinases use extracellular ATP as a phosphate donor to phosphorylate endogenous cell surface proteins as well as soluble proteins and have been implicated in a number of biological phenomena including cell adhesion (52), Ca 2ϩ influx (53), neurotransmitter uptake (54,55), synaptogenesis (41), neurite outgrowth (45,56), synaptic plasticity, and long term potentiation (47). We reported previously that the developmental change in the localization of NGC on the Purkinje cells correlates well with synaptogenesis of the climbing fiber system on Purkinje cells (16), suggesting that NGC is involved in the selective synaptogenesis in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%